2004
DOI: 10.1165/rcmb.2003-0384oc
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of c-Jun N-terminal Kinase and p38 Kinase Pathways in Endothelial Cells

Abstract: The rapid and transient induction of E-selectin gene expression by inflammatory tumor necrosis factor (TNF)-alpha in endothelial cells is mediated by signaling pathways which involve c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK) kinase pathways. To explore this regulation, we first observed that in the continuous presence of cytokine TNF, activation of JNK-1 in both nuclear and cytoplasmic compartments peaked at 15-30 min, with activity returning to uninduced levels by 60 min. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…This implies that the macrophage is an important site of action of GCs in one experimental model of acute inflammation, and that important anti-inflammatory effects are dependent on inhibition of p38 MAPK. Recent studies also implicate DUSP1 in the anti-inflammatory response to GCs in endothelial cells (Wadgaonkar et al, 2004;Furst et al, 2007), microglia (Zhou et al, 2007) and human airway smooth muscle cells (Issa et al, 2007). However, it is not known whether DUSP1 contributes to the anti-inflammatory effects of…”
Section: A Clarkmentioning
confidence: 99%
“…This implies that the macrophage is an important site of action of GCs in one experimental model of acute inflammation, and that important anti-inflammatory effects are dependent on inhibition of p38 MAPK. Recent studies also implicate DUSP1 in the anti-inflammatory response to GCs in endothelial cells (Wadgaonkar et al, 2004;Furst et al, 2007), microglia (Zhou et al, 2007) and human airway smooth muscle cells (Issa et al, 2007). However, it is not known whether DUSP1 contributes to the anti-inflammatory effects of…”
Section: A Clarkmentioning
confidence: 99%
“…We searched for novel substrates using the "substrate-trap" technique that has been used to identify novel protein substrates of other phosphatases (48). MKP-1 is critical for the regulation of inflammatory genes (7,55), as is chromatin, which contains an octamer composed of a dimer-doublet histone H2A/H2B and tetramer of H3 and H4 core histone proteins. Histone modifications, such as phosphorylation, acetylation, methylation, ubiquitination, ADP-ribosylation, and glycosylation at the amino terminus of histone tails are important in regulating chromatin structure and thereby gene expression (25).…”
mentioning
confidence: 99%
“…We observed that the application of high shear to EC led to the induction of MKP-1, an intracellular protein that is known to repress endothelial activation by inhibiting the activities of both p38 and JNK 6 . This finding was validated in vivo by studies of the murine aorta which demonstrated that MKP-1 was expressed in EC in regions exposed to high shear but was absent at adjacent sites exposed to relatively low shear.…”
Section: Discussionmentioning
confidence: 91%
“…LPS, endotoxin), which may be circulating due to intercurrent infections 3 , activate both NF-κB and mitogen activated protein (MAP) kinase signalling pathways which co-operate to induce pro-inflammatory proteins such as VCAM-1 4,5 . JNK and p38 MAP kinases play an important role in vascular inflammation [6][7][8][9][10] . They are activated in EC in response to pro-inflammatory stimuli by dual phosphorylation of Thr-X-Tyr motifs within the phosphorylation loop 10 .…”
Section: Introductionmentioning
confidence: 99%